2015
DOI: 10.1039/c5ra05443e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of H2S removal on γ-Al2O3 surfaces of different hydroxyl coverage

Abstract: The sulfurized processes of H 2 S on dehydrated (100) and (110) as well as partially hydrated (110) surfaces of g-Al 2 O 3 were investigated using a periodic density functional theory method. The adsorption configurations of possible intermediates and the potential energy profiles of reaction are depicted. Our results show that H 2 S adsorbs preferentially on the Al site along with the S bond, and the adsorption energies are À32.52 and À114.38 kJ mol À1 on the dehydrated (100) and (110) surfaces, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…53 In total, thirty-nine different adsorption congurations were investigated in this work (thirteen facets, as listed in ref. 58, and three SO 2 initial congurations per surface). The adsorption energy was calculated for the different congurations, either the cobalt-or phosphorus-terminated CoP surfaces.…”
Section: So 2 Adsorptionmentioning
confidence: 99%
“…53 In total, thirty-nine different adsorption congurations were investigated in this work (thirteen facets, as listed in ref. 58, and three SO 2 initial congurations per surface). The adsorption energy was calculated for the different congurations, either the cobalt-or phosphorus-terminated CoP surfaces.…”
Section: So 2 Adsorptionmentioning
confidence: 99%
“…Such studies frequently necessitate the use of in situ/operando analysis techniques. Theoretical and computational approaches can provide synergistic insights at atomistic resolution, assuming that the models implemented are reliable. Of the computational approaches available, studies of γ-alumina surfaces to-date are dominated by density functional theory (DFT) and ab initio molecular dynamics (AIMD) for nonaqueous and aqueous systems; studies of the latter are fewer, and mostly the domain of AIMD. While the level of resolution accessible to DFT and AIMD is exquisitely detailed, the system sizes and time scales attainable using these methods remains limited due to the high computational demands.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Rohmann et al 35 investigated molecular interaction of carbon monoxide with hydroxylated alumina surface, reporting that molecular CO exhibits strong interaction with a 25% degree of hydroxylated surface and this interaction is signicantly stronger when compared with that over the clean dehydrated alumina. In a follow-up study on H 2 S removal via g-Al 2 O 3 surfaces with different hydroxyl coverage, Ren et al 36 revealed that, the bonding strength of H 2 S on hydrated alumina surface is lower than that the over a dehydrated termination. For example, calculated binding energy for 8.9 OH per nm 2 hydroxyl coverage for g-Al 2 O 3 (110) amounts to À68 kJ mol À1 whereas the corresponding value of the dehydrated surface stands at À114 kJ mol À1 .…”
Section: Introductionmentioning
confidence: 99%